Preparation of core/shell organic–inorganic hybrid polymer nanoparticles and their application to toughening poly(methyl methacrylate). Issue 54 (20th October 2021) - Xia, Jia; Luo, Xia; Huang, Jin; Ma, Jiajun; Yang, Junxiao
Abstract : Core/shell organic–inorganic hybrid polymer nanoparticles are synthesized by micellar nucleation, core enlarged polymerization and a grafting reaction in the system. Abstract : On account of the utility of poly(methyl methacrylate) (PMMA) as a glass substitute, toughening of PMMA has attracted significant attention. Brittle failure can often be avoided by incorporating a small fraction of filler particles. Core–shell composite particles composed of a rubbery core and a glassy shell have recently attracted interest as a toughening agent for brittle polymers. Here, core/shell organic–inorganic hybrid polymer nanoparticles (Si-ASA HPNs) with a silicone-modified butyl acrylate copolymer (PBA) core and a styrene-acrylonitrile copolymer (SAN) shell were used to toughen PMMA. Silicone plays dual roles as a compatibilizer and a chain extender, and it not only improves interfacial adhesion between the PBA particles and SAN copolymer, but it also increases chain entanglement of poly(acrylonitrile-styrene-acrylate) (ASA). The mechanical properties of the PMMA/ASA alloys strongly depend on the Si content, and the impact strength and elongation at break greatly improve when silicone-modified ASA is added. However, this is accompanied by loss of rigidity. Specifically, the PMMA/ASA-2 composite exhibits a good balance between toughness and rigidity, indicating that ASA-2 with 5 wt% KH570 is the most suitable impact modifier. This research provides a facile and practical method to overcome the shortcomings of ASA and promote its application in a wider range of fields.